Penanganan kembali slurry keluaran digester biogas dengan substrat awal manure sapi perah dan biji pepaya untuk meningkatkan produksi methan - Nain Ufidiyati; Ibnu Adib Fuady; Sutaryo Sutaryo; Agung Purnomoadi (Jurnal Ilmu Peternakan Terapan, 2023)
Co-substrate of papaya seeds (PS) with dairy cow manure (DCM) resulted an increase of organic matter (OM) content and not all OM could be digested properly in the continuous digester. This research was conducted to measure methane production of slurry that study. The experiment used MSP, BP, NaOH, batch type digester with completely randomized design. The treatments were R1 (100% DCM), R2 (95% DCM and 5% PS non germination) and R3 (95% DCM and 5% PS germination) with 5 replications. Data were analysed using analysis of variance. The observed variables were methane production, pH value, dry matter reduction (DMR) and OM reduction (OMR). Methane production showed significantly different (P<0.05), namely: 5.28; 7.19 and 6.26 l/l for R1, R2 and R3. The limited hydraulic retention time of substrate in continuous digester caused not all of the OM in R2 and R3 to be properly digested and is still left in the slurry. The decrease methane production of R3 than R2 was due to better nutrient content of R2 so that it was digested better while in the continuous digester. The higher DMR, OMR and methane production in R2 and R3 than R1 indicate that the use of BP as a co-substrate with DCM can increase the OM content and its quality and some of OM is still left in the slurry.